ANALISIS SISTEM PENGENDALIAN MANAJEMEN DALAM UPAYA MENINGKATKAN KINERJA MANAJEMEN PRODUKSI ( STUDI KASUS PADA PT. LIEBRA PERMANA BAWEN KABUPATEN SEMARANG) - Ari Arifah Ifah (Universitas Muhammadiyah Tangerang, 2021)
Management Control System is a system used by management to ensure that an organization has implemented strategies effectively and efficiently in order to achieve predetermined goals. In achieving these objectives, one of the companies must pay attention to and evaluate the performance of company management. This is very important to do in order to maintain the sustainability of the company. The purpose of this study was to determine the application of management control systems, management performance evaluation, and strategies in improving management performance applied to PT LIEBRA PERMANA. The method used is descriptive qualitative method using a comparative analysis between theory and practice where data is collected and analyzed and then conclusions are drawn. Based on the results of the analysis, it can be concluded that the management control system at PT LIEBRA PERMANA is already running well, and performance evaluation and strategic planning are carried out through each division so as to improve management performance and productivity, especially production management at PT LIEBRA PERMANA.